Readiness for Smart Learning in Indonesia’s Islamic Universities - Susanto Susanto; Apri Wardana Ritonga; Ayu Desrani; Yohan Rubiyantoro (AL-ISHLAH: Jurnal Pendidikan, 2025)
Technological advancements have driven significant innovations in education, notably through smart learning systems. In Indonesia, Islamic universities are increasingly adopting smart learning to enhance the quality of higher education. This study examines their readiness for smart learning implementation. A mixed-method approach combined quantitative and qualitative data collection. Questionnaires were distributed via Google Forms to 608 students, and additional insights were gathered through interviews. Quantitative data were analyzed using percentage calculations and descriptive analysis, while qualitative findings were thematically organized. The study found that the implementation of smart learning in Islamic universities is moderately effective across four key areas: learning management systems, personalized learning, assessment, and library management systems. Questionnaire scores for all aspects exceeded 6.00, indicating a generally positive perception. Nevertheless, issues such as inadequate infrastructure and insufficient faculty readiness emerged as significant challenges. The findings suggest that Islamic universities in Indonesia are adapting to technological changes but require ongoing development to integrate smart learning practices fully. Addressing infrastructure and faculty training gaps is essential to enhance educational quality, graduate competencies, and institutional competitiveness.